The Influence of The Global Reporting Initiative, Sustainability Accounting Standard Board and Carbon Emission Disclosure on the Sustainable Development Goals in Southeast Asia in the Islamic Perspective in 2021 And 2022 - Wiraputra, Jhody; Supaijo, Supaijo; Sisdianto, Ersi (SEAN Institute, 2024)
This study aims to analyze the effect of the Global Reporting Initiative, Sustainability Accounting Standard Board and Carbon Emission disclose simultaneously on Sustainable Development Goals in sustainable reporting of Southeast Asian countries, as well as Islamic views on Sustainable Development Goals. Using panel data with 5 countries in Southeast Asia or ASEAN members included in the Sustainability Count of PricewaterhouseCoopers (PwC) both GRI, SASB and CDP for the period of 2021 and 2022 the analysis tools used in this study are multiple linear regression with variables Global Reporting Initiative, Sustainability Accounting Standards and Carbon Emissions Disclosure as independent variables, while Sustainable Development Goals as dependent variables. The results of this study provide insight into the factors that affect the achievement of Sustainable Development Goals